Short communication. Biological fixation of nitrogen and N balance in soybean crops in the pampas region - Diciocco, C.=700 1 Coviella, C.; Penon, E.; Diaz Zorita, M.
(Es, En)
Ilus., 23 ref.
Keywords: GLYCINE MAX; FIJACION DEL NITROGENO; TECNICA DE TRAZADORES; SIEMBRA DIRECTA; RENDIMIENTO; LABRANZA CONVENCIONAL; ESPAÑA